Jenis Fungi Yang Terdapat Pada Serasah Daun Acacia mangium - Samingan Samingan (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
Fungi are cosmopolite organisms that able to grow in any substrates such as Acacia’s leaf litters. The aim of this research was to identify the fungi from litter layers. Identifying was done by observing fungal structure and colonies characters on PDA. Isolates which were estimated as Basidiomycetes tested by laccase test and peroxidase test. Based on those characters, there was 7 isolates from  genera of Pythium belongs to Mastigomycetes, 1 isolate from Basidiomycetes and 6 genera belongs to Deuteromycetes, i.e. 5 isolates of Penicillium, 10 isolates of Aspergillus, 5 isolates of Trichoderma, 2 isolates of Fusarium, 1 isolate of Geotrichum and 1 isolate of  Phialophora. Seven other isolates were unidentified.